Optimalisasi Limbah Padi Sebagai Energi Alternatif untuk Pemberdayaan Ekonomi dan Pencegahan Stunting - Abdul Arif; St. Syahdan; Siti Maria Ulva; Dady Sulaiman; Ayu Lingga Ratna Sari (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Stunting remains a significant child health issue in Indonesia, particularly in Bulungan Regency, with prevalence rates demanding multisectoral interventions. Low socioeconomic factors play a crucial role in stunting incidence due to limited access to nutritious food and healthcare services. This community service aims to optimize rice waste, especially straw and husks, as alternative energy sources to empower local economies and prevent stunting in Sajau Hilir Village. A participatory method was employed through direct education and training involving the PKK women's group. The activities focused on socializing the processing of rice waste into economically valuable products such as rice husk charcoal briquettes and biosensitizers from rice straw. The results showed increased knowledge and skills among community members in converting waste into environmentally friendly and marketable alternative energy products. Utilizing rice waste not only reduces agricultural waste but also opens new economic opportunities sustainably and independently, strengthening family economic resilience and enhancing the ability to meet children's nutritional and healthcare needs. Thus, optimizing rice waste provides a strategic contribution to integrating environmental management and accelerating stunting reduction through local economic empowerment. Recommendations include strengthening community institutions, developing joint business units, and fostering collaboration between universities and local governments.